2017
DOI: 10.18332/tpc/70873
|View full text |Cite
|
Sign up to set email alerts
|

Graphic health warnings and their best position on waterpipes: A cross-sectional survey of expert and public opinion

Abstract: INTRODUCTION Our aim was to assess the visibility and efficiency of graphic health warnings (GHWs) on waterpipe tobacco packs (WTPs) and to explore other more effective places to display them for better impact. We also evaluated the visibility of GHWs when placed on the waterpipe device. METHODS We conducted 3 cross-sectional study phases using face-to-face survey questionnaires in 2014-2015. Phase I surveyed 31 tobacco control experts, while Phase II surveyed 700 participants and Phase III surveyed 348 from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
(40 reference statements)
2
11
0
Order By: Relevance
“…The content of the existing warnings studied in this research were about smoking in general and not WTS in particular, although they appeared on WTPs. A recent report of the WHO recommended waterpipe-specific product labelling to improve the intended effects of the health warnings [5], as well as more recent quantitative [26,27,32] and qualitative [28,29,30, 31] research on PHWs on WTPs. Warnings with waterpipe-specific text and images may render PHWs on WTPs more believable, especially among participants who do not react affectively to PHWs or are resistant to changing their WTS habits or less concerned about WTS health hazards.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The content of the existing warnings studied in this research were about smoking in general and not WTS in particular, although they appeared on WTPs. A recent report of the WHO recommended waterpipe-specific product labelling to improve the intended effects of the health warnings [5], as well as more recent quantitative [26,27,32] and qualitative [28,29,30, 31] research on PHWs on WTPs. Warnings with waterpipe-specific text and images may render PHWs on WTPs more believable, especially among participants who do not react affectively to PHWs or are resistant to changing their WTS habits or less concerned about WTS health hazards.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, health warning labelling of non-cigarette tobacco products, including waterpipe tobacco, remain understudied. To our knowledge, few published studies have examined the impact of waterpipe tobacco PHWs: two online surveys from Canada and the US—both countries do not require PHWs on waterpipe tobacco packs (WTPs) [26,27], four qualitative studies from the UK, Egypt and the EMR [28, 29, 30, 31] and one survey from Egypt that explored expert and public opinion of the visibility of existing PHWs on WTPs and their best likely position on waterpipes [32]. The first two studies were experimental and tested hypothetical text-only versus PHWs, with limited effect on established waterpipe users.…”
Section: Introductionmentioning
confidence: 99%
“… 37 The Egyptian survey reported that only half of 1048 waterpipe smoker and non-smoker participants thought that existing PHWs on WTPs were visible; they expressed varying views on the effectiveness of WT PHWs across several measures (such as salience, credibility, perceived harm, affective reactions). 39 However, this survey did not examine whether participants perceived existing WT PHWs effective in deterring uptake or quitting of WTS.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, only a few studies have examined the impact of WT PHWs: two online surveys from Canada 34 and the USA, 35 three qualitative studies from the UK, 36 Egypt 37 and the EMR 38 and one recent Egyptian survey. 39 The two online surveys tested hypothetical warnings shown on computer screens rather than on WTPs and examined the effectiveness of text-only versus PHWs. 34 35 Both studies found that PHWs had a modest impact on established waterpipe smokers.…”
Section: Introductionmentioning
confidence: 99%
“…In US cigarette package warning exposure studies, exposure ranged from 89.9% of youth smokers reporting any exposure 19 to 28% of US adults reporting exposure often or very often. 20 However, as one cross-sectional survey study in Egypt 21 and one qualitative study in London 22 each found, warnings on waterpipe tobacco packages might not be noticed because users within waterpipe cafés (where a significant portion of waterpipe smoking takes place) report limited exposure to waterpipe tobacco packaging. This, in addition to lack of mandated waterpipe warnings in the USA, prior to August 2018 (compared with mandated warnings for cigarettes since the 1960s), we hypothesise reported waterpipe package warning exposure will be relatively low.…”
Section: Introductionmentioning
confidence: 99%